Investigating allometric scaling and trade-off between sensory organs in European butterflies - Li,Min (2025)
Understanding how organisms allocate limited resources among competing traits is a central issue in evolutionary biology. In this thesis, I test whether butterflies have an energetic trade-off between the high-cost sensory traits, compound eyes and antennae. Such a trade-off would be predicted by the Expensive Tissue Hypothesis. We used high-resolution 3D micro-CT data from 233 museum specimens (representing 59 species of European butterflies) to quantify the trait sizes of sensory (eyes and antennae) and various somatic traits (thorax, abdomen and forewing). Allometric analyses revealed that eyes and antennae exhibited negative allometric scaling with different body size proxy, suggesting that individuals with larger body sizes invest relatively lower in sensory organs. Contrary to predictions, eyes and antennae show significant positive correlations after controlling for body size and phylogenetic relatedness, with no trade-offs found between the two. My analyses also suggests that the choice of body size proxy metrics slightly affected slope estimates and body size corrected eye and antenna size, suggesting consideration should be given to the which body size metric is used when doing allometry. In future, testing of trade-off between brain and sensory structure, as well as other expensive tissues such as the gut (as expected by the Expensive Tissue Hypothesis), will be interesting. Finally, identifying ecological drivers mediating trade-offs or morphological diversification of sensory traits would provide deeper understanding on the evolution of these key expensive traits.